A Comparative Analysis of Quantum Computing and Classical Computing in Solving Linear Algebra Problems - Andrea Montemurro; Marco F. Durante; Silvia Giordano (International Journal of Science and Mathematics Education, 2024)
Quantum computing offers promising alternatives to classical approaches for solving complex linear algebra problems. This paper presents a comparative study of the performance of quantum algorithms versus classical algorithms in solving systems of linear equations and matrix operations. Through simulation and analysis, we demonstrate that while quantum computing holds advantages in specific problem sets, classical computing remains efficient for general applications. These findings highlight the current limitations and potential of quantum computing.